Characteristics Characteristic Of Chemical Rice Analog Based On Arrowroot Starch (Maranta arundinacea) With The Addition Of Kelor Leaf (Moringa oleifera) and Broccoli Pulp - Damat Damat; Ayu Andini; Mujianto Mujianto (Food Technology and Halal Science Journal, 2019)
This research studied the effect of different sources and the percentage of chlorophyll on the quality of analog rice. This study uses Nested design with the first factor as the nest is the source of chlorophyll and second as a nested factor is the concentration of chlorophyll (5%, 7.5%, and 10%). The analysis tested was moisture content, ash, protein, lipid, fiber, carbohydrate, total calories, antioxidant activity, and total chlorophyll. After cooking, the rice conducted the sensory test (appearance, flavor, aroma, texture), antioxidant activity, and total chlorophyll. The results showed that the addition of chlorophyll sources and the percentage of chlorophyll affect moisture, ash, protein, fat, carbohydrate, fiber, total calories, antioxidant activity, total chlorophyll, and the appearance of analog rice as well as no effect on the flavor, texture, and aroma of analog rice. This research resulted that the lowest moisture of 8.22% derived from the treatment of 5% kelor leaf, the highest carbohydrate of 90.58% from the treatment of 5% broccoli pulp, the highest antioxidant activity in rice of 22.118% from treatment 10% broccoli pulp as well as the highest chlorophyll in rice of 10%, 2.72 mg/L from the treatment of kelor leaf.